In Christ, in Colossae : sociological perspectives on Colossians - Tidball, Derek (Milton Keynes : Paternoster, 2011)
The purpose of the book is to apply major sociological discussions of the New Testament to the letter of Colossians with the objectives of (a) introducing those who do not know the rich literature on the sociology of the New Testament to some concrete examples of it and the illumination it provides; (b) providing a systematic sociological approach to Colossians; and (c) engaging with and evaluating the scattered discussion that has been held with regard to Colossians. The result is a rich engagement with the Letter to the Colossians and an encouragement to look again at our own Christian communities.
Includes bibliography (p. 159-171).
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Social scientific criticism